Effective Language in Communication - Siti Khasinah, Barep Sarinauli, Cut Putri Ellyana, Nashriyah, Syafira Yunidar, Siti (JKA, 2024)
Language and transmission are closely related in human communication. Researching language as a means of communication helps us understand verbal and nonverbal transmissions. Verbal correspondence delivered in a structured or spoken manner is often ineffective without good nonverbal transmission. In management, the organizational structure that corresponds to the development of the business favors rationalization and increased productivity. Language is the main tool for conveying messages, ideas and goals, and delivery is a need of society. The study of language involves skills such as expression, data collection, research, influence, and transfer. An understanding of language theory that supports the communication process is essential for effective communication. The research method used is Library and literature research. The training with lecture method, question and answer, and discussion was followed by the principal of Central Aceh. The results showed an increase in knowledge and active participation of participants.